Strategi Pengembangan Usaha Kerajinan Bambu di Wilayah Kampung Pajeleran Sukahati Kecamatan Cibinong Kabupaten Bogor - Setiawan, Budi (Jurnal Manajemen dan Organisasi, 2010)
Bamboo handicraft business at rural areas, of Pajeleran Sukahati, Cibinong of Bogor district, Indonesia is estimated to have lasted since the 1960s carried from generation to generation. Some types of bamboo handicraft products routinely produced are variety of furniture products like tables and chairs. This study aims to know the description of the existence of craftsmen, the strengths and weaknesses as well as strategies that can be owned implemented for business development. Based on survey results revealed that the total value of IFE matrix owned by the craftsman is 3.00 and the total value of EFE matrix is 3.05. Further analysis of these results is phase matching, which produces information that the presence of artisans into the first cells that means grows and develops. There are three alternative strategies that can be applied by the craftsmen in developing their business are: 1). Market penetration; 2). Development or expansion of the market; and 3). Products development. Based on QSPM result, products development has a highest score of Total Attractive Score (TAS), so it’s has been chosen as the most recommended strategy.